PENGGUNAAN SPLINT EKSTRAKORONAL PADA PERAWATAN PERIODONTITIS KRONIS (LAPORAN KASUS) - Puspito Ratih Hardhani (B-Dent: Jurnal Kedokteran Gigi Universitas Baiturrahmah, 2022)
Introduction: The use of splints is one of the stages of treatment in periodontitis accompanied by tooth mobility. Based on the location of the splint, there are two types of splinting, namely extra-coronal and intra-coronal splinting. Treatment using splints is based on the condition of the periodontal tissue, occlusion, articulation, and the severity of periodontitis. This article discusses two case reports regarding the management of chronic periodontitis with tooth mobility. Case report and Management: The first case was a 45-year-old female patient with a diagnosis of localized chronic periodontitis in teeth 32, 31, and 41 with tooth mobility. Initial treatments were scaling-root planning (SRP), plaque control, occlusion adjustment, endodontic treatment, and extra-coronal splinting using fiber-reinforced and composite resins. The second case was a 47-year-old woman with controlled diabetes, and a diagnosis of localized chronic periodontitis on teeth 12, 11, 21, 33, 32, 31, 41, and 42. Initial treatment was SRP, plaque control, occlusion adjustment, and extra-coronal splinting using 0.03 diameter wire and composite resin. The patient stated that she was satisfied with the results of the initial treatment carried out because the teeth that experienced mobility were maintained and remained in the oral cavity. The next therapy is periodontal flap surgery accompanied by the addition of bone grafts. Conclusion: The use of extra-coronal splints in the initial therapy phase of chronic periodontitis cases aims to stabilize loose teeth. Extra-coronal splinting treatment is carried out to support the success of periodontitis treatment.